Abdominal Circumference or Gastric Residual Volume as Measure of Feed Intolerance in VLBW Infants. Issue 2 (February 2015) - Kaur, Avneet; Kler, Neelam; Saluja, Satish; Modi, Manoj; Soni, Arun; Thakur, Anup; Garg, Pankaj
ABSTRACT: Background: The aim of the study was to compare prefeed abdominal circumference (AC) and gastric residual volume (GRV) as a measure of feed intolerance in very-low-birth-weight infants (VLBW). Methods: Eighty VLBW infants were randomized to 2 groups; feed intolerance was monitored by measuring either GRV group or prefeed AC group. The primary outcome was time to full enteral feeds (180 mL · kg −1 · day −1 ). Other main outcome measures were feed interruption days, duration of parenteral nutrition, incidence of culture positive sepsis, necrotizing enterocolitis, mortality, and duration of hospital stay. Results: The median (interquartile range) time to achieve full feeds was 10 (9–13) versus 14 (12–17.5) days in AC and GRV groups, respectively ( P < 0.001). Infants in AC group had fewer feed interruption days (0 [0–2] vs 2.0 [1, 5], P < 0.001) and shorter duration of parenteral nutrition ( P < 0.001). The incidence of culture-positive sepsis in AC and GRV groups was 17.5% and 30 %, respectively ( P = 0.18). Duration of hospital stay and mortality were comparable in both the groups. Conclusions: Prefeed AC as a measure of feed intolerance in VLBW infants may shorten the time taken to achieve full feeds.